Public-private partnership as a tool to foster business innovation activities in the digital technologies field - D. V. Baibulatova (Ekonomika Nauki)
The unprecedented sanctions imposed against Russia included restrictions on the supply of high-tech products and services have updated issues of ensuring the technological independence of Russia in the digital technologies field by increasing private sector involvement in innovation processes and relying on our own developments. Cooperation between the public and private sectors within the framework of public-private partnership (PPP) can become an effective tool for achieving this goal. The article analyses United States experience in use of PPPs in the digital technologies field as well as Russian practice of using this mechanism to foster business innovation activities. Analyzing specific PPP mechanisms (models), the author identifies their key features, which determine the possibilities of their application in the development and implementation of government-business cooperation projects in the digital technologies field. It is concluded that, unlike the United States, the leading country in digital development, PPP models are not used enough in Russia, which is explained, among other things, by the presence of administrative and legal barriers as well as problems with goal-setting.